U.S. policing as racialized violence and control: a qualitative assessment of black narratives from Ferguson, Missouri - Williams, Jason M. (Journal of ethnicity in criminal justice, 2021)
U.S. policing has long been captured within a master narrative of colorblind consensus; however, distinct lived experiences between community groups depict grave disparities in law enforcement experiences and perceptions. Orthodox conceptions of law enforcement ultimately silence marginalized voices disproportionately affected by negative contacts with law enforcement. Centering data in critical theory, this study will present thematic results from semi-interviews gathered in Ferguson, M.O., during a critical ethnographic research project. Themes reveal experiences and perceptions of racialized and violent policing, the unique position of Black officers, and regard for the impact police have on children. Results also help to foreground new epistemic frameworks for contextualizing U.S. policing along racial and geographic contours.